2021
DOI: 10.3390/ma14143823
|View full text |Cite
|
Sign up to set email alerts
|

Magnetron Sputtering vs. Electrodeposition for Hard Chrome Coatings: A Comparison of Environmental and Economic Performances

Abstract: The coating of materials with specific films is widely used to improve material properties and many technologies exist to perform it. In the last few years, the replacement of wet electrodeposition processes has been continuously encouraged in the EU due to the problematic waste management linked to those processes. In this paper, magnetron sputtering is studied as an alternative to conventional electrodeposition by comparing the technologies’ environmental impacts and costs. From the study, it appears that wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…57 The cost of the IL-based electrolyte was obtained from a cost analysis of Al-gra. 11 The cost of the CC coating was obtained from costs of the thin films of Cr, 58 adjusted for the sputtering conditions for Cr 2 N. 51 BatPaC provides costs for purchased items and nonmaterials. The latter include costs of depreciation (for a ''Gigafactory'' producing 100 000 packs i.e.…”
Section: Economic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…57 The cost of the IL-based electrolyte was obtained from a cost analysis of Al-gra. 11 The cost of the CC coating was obtained from costs of the thin films of Cr, 58 adjusted for the sputtering conditions for Cr 2 N. 51 BatPaC provides costs for purchased items and nonmaterials. The latter include costs of depreciation (for a ''Gigafactory'' producing 100 000 packs i.e.…”
Section: Economic Performancementioning
confidence: 99%
“…64 The GWP of the CC-coating was calculated from LCA for sputtered Cr. 58 The CSPs for virgin crust elements were used, except for Cl and Cu for which the CSPs were weighted to also account for supplies from other sources, sea-water and recycling, respectively. 39 For the CSP of the electrical BOS and PCS, the electronics were assumed to have the compositions as inverters in EVs.…”
Section: Environmental Performancementioning
confidence: 99%
“…35,36 Beyond providing excellent control over coating uniformity, thickness, and composition, physical vapor deposition methods produce less waste and are less labor-intensive than traditional electrodeposition methods, thus making them cost-competitive, despite higher capital costs. 37 Using a microfluidic gas diffusion electrolyzer, we observed that EB-Cu coatings generally provide better performance than the MS-Cu catalyst coatings in terms of current density, selectivity, and energy efficiency, with an optimum thickness of 400 nm where the energy efficiency (i.e., sum over the Faradaic efficiency times theoretical cell potential divided by the applied potential for all eCO 2 RR products; for details, see below) reaches 51% (56.5% for eCO 2 RR and HER combined). Scanning and transmission electron microscopy (SEM/TEM), Rutherford backscatter analysis (RBA), electrochemical surface area (ECSA), and contact angle measurements suggest that the generally better eCO 2 RR performance of EB-Cu coatings correlates with the GDL/Cu catalyst morphology, making the EB-Cu catalyst layer more hydrophobic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both methods have the potential for large-scale production, allow for direct coating of the electrocatalyst on the GDL, and provide excellent thickness control and coating uniformity combined with a high specific surface area. More importantly, they are also scalable to very large electrode areas (∼10 4 cm 2 ) , and enable precise control over morphology and porosity. , PVD methods also provide a path forward to efficient integration and compositional tuning of Cu alloy catalysts, including nonthermodynamic equilibrium alloy compositions that are difficult to synthesize and integrate otherwise. , Beyond providing excellent control over coating uniformity, thickness, and composition, physical vapor deposition methods produce less waste and are less labor-intensive than traditional electrodeposition methods, thus making them cost-competitive, despite higher capital costs . Using a microfluidic gas diffusion electrolyzer, we observed that EB-Cu coatings generally provide better performance than the MS-Cu catalyst coatings in terms of current density, selectivity, and energy efficiency, with an optimum thickness of 400 nm where the energy efficiency (i.e., sum over the Faradaic efficiency times theoretical cell potential divided by the applied potential for all eCO 2 RR products; for details, see below) reaches 51% (56.5% for eCO 2 RR and HER combined).…”
Section: Introductionmentioning
confidence: 99%
“…However, these approaches require more steps and yield thicker layers, and there are also several concerns from the health, safety, and environmental points of view. 14 As recently reviewed, chemical vapor deposition (CVD) techniques such as atomic layer deposition (ALD) are extremely valuable for membrane science and have been tested for many applications, including gas separation and water filtration, biosensing, and catalysis. 15−17 ALD is based on the sequential use of surface-limited, self-terminating chemical reactions that take place in a cyclewise fashion, thus allowing one to prepare conformal and high quality films at the nanoscale on complex substrates and at low temperatures.…”
Section: Introductionmentioning
confidence: 99%